2003
DOI: 10.1016/s0002-9440(10)63646-2
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Induces Cytoprotection in Rat Orthotopic Lung Transplantation via Anti-Inflammatory and Anti-Apoptotic Effects

Abstract: Successful lung transplantation has been limited by the high incidence of acute graft rejection. There is mounting evidence that the stress response gene heme oxygenase-1 (HO-1) and/or its catalytic by-product carbon monoxide (CO) confers cytoprotection against tissue and cellular injury. This led us to hypothesize that CO may protect against lung transplant rejection via its anti-inflammatory and antiapoptotic effects. Orthotopic left lung transplantation was performed in Lewis rat recipients from Brown-Norwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
161
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 205 publications
(169 citation statements)
references
References 47 publications
5
161
2
1
Order By: Relevance
“…Our laboratory and others have shown that HO-1 induction in response to cellular and tissue stress, in vitro or in vivo, is not only a reliable marker of cellular injury but also a physiologic response to defend against the inciting stress or cellular insult. Recently, our laboratory has provided evidence that CO, a major by-product of heme catalysis by HO-1, mediates the protective effect of HO-1 (15)(16)(17)(18)(19). Thus, in view of our observation that HO-1 was markedly increased in VILI, we sought to assess whether CO could be responsible in mitigating VILI.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our laboratory and others have shown that HO-1 induction in response to cellular and tissue stress, in vitro or in vivo, is not only a reliable marker of cellular injury but also a physiologic response to defend against the inciting stress or cellular insult. Recently, our laboratory has provided evidence that CO, a major by-product of heme catalysis by HO-1, mediates the protective effect of HO-1 (15)(16)(17)(18)(19). Thus, in view of our observation that HO-1 was markedly increased in VILI, we sought to assess whether CO could be responsible in mitigating VILI.…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism by which HO-1 or CO mediate a cytoprotective effect is via its potent antiinflammatory properties (13,14). Our laboratory has recently demonstrated that exogenous administration of low concentration of inhaled CO can markedly decrease lung inflammation and confer potent cytoprotection in various tissue injury models (15)(16)(17)(18)(19).…”
Section: Abstract: Cytokines; Heme Oxygenase-1; P38 Mapkmentioning
confidence: 99%
See 3 more Smart Citations